PENGARUH PENGALAMAN KERJA, LINGKUNGAN KERJA, DAN TEKANAN ANGGARAN WAKTU TERHADAP AUDIT JUDGMENT - Jayanti, I Gusti Agung Diah Dwi; Datrini, Luh Kade; Miati, Ni Luh Putu Mita (KRISNA: Kumpulan Riset Akuntansi, 2025)
Audit judgment is the auditor's policy in assessing the results of the examination that affect the fairness of financial statements. Numerous cases related to audit judgment by the Supreme Audit Agency (BPK)have raised doubts among users of BPK audit reports. The differing results found by previous researchers have led to inconsistencies in research and a lack of studies investigating the influence of the work environment on audit judgment. Therefore, researchers see an opportunity to re-examine the factors that influence audit judgment. This study aims to identify the influence of work experience, work environment, and time budget pressure on audit judgment among BPK auditors in Bali Province. Data were collected through a survey of 50 BPK auditors in Bali Province. The sampling method used was non-probability sampling with a purposive sampling technique, and the analysis was conducted using Structural Equation Model (SEM) with the SmartPLS analysis tool. The results of the study indicate that the work experience variable has a significant positive influence on audit judgment. However, the work environment and time budget pressure variables do not have a significant influence on audit judgment. This study has theoretical and practical implications for the BPK in Bali Province.